RNA-binding protein Nocte regulates Drosophila development by promoting translation reinitiation on mRNAs with long upstream open reading frames. - Zhang, T.; Xue, Y.; Su, S.; Altouma, V.; Ho, K.; Martindale, J.L.; Lee, S.K.; Shen, W.; Park, A.; Zhang, Y.; De, S.; Gorospe, M.; et al. (Nucleic Acids Research, 2024)
RNA-binding proteins (RBPs) with intrinsically disordered regions (IDRs) are linked to multiple human disorders, but their mechanisms of action remain unclear. Here, we report that one such protein, Nocte, is essential for Drosophila eye development by regulating a critical gene expression cascade at translational level. Knockout of nocte in flies leads to lethality, and its eye-specific depletion impairs eye size and morphology. Nocte preferentially enhances translation of mRNAs with long upstream open reading frames (uORFs). One of the key Nocte targets, glass mRNA, encodes a transcription factor critical for differentiation of photoreceptor neurons and accessory cells, and re-expression of Glass largely rescued the eye defects caused by Nocte depletion. Mechanistically, Nocte counteracts long uORF-mediated translational suppression by promoting translation reinitiation downstream of the uORF. Nocte interacts with translation factors eIF3 and Rack1 through its BAT2 domain, and a Nocte mutant lacking this domain fails to promote translation of glass mRNA. Notably, de novo mutations of human orthologs of Nocte have been detected in schizophrenia patients. Our data suggest that Nocte family of proteins can promote translation reinitiation to overcome long uORFs-mediated translational suppression, and disruption of this function can lead to developmental defects and neurological disorders.